Structured telephone training improves telephone competence in prelingually deafened children with a cochlear implant. (September 2015) - Mathur, Kavita; Jeyaraman, Janani; Mathur, Madhavendra Chandra; Batra, Ridhima
Abstract : Objective: The aim of the study is to assess the efficacy of a 6-month telephone use training programme in prelingually deafened children with a cochlear implant (CI). Methods: Eleven children with a CI aged between 3.5 and 8 years participated in a step-by-step telephone training programme. After completion of 3 months of formal training provided by a special education professional, parents continued telephone training at home for 3 months and kept records. The outcomes of the entire 6-month telephone training were measured at three intervals using the Telephone Profile, the Iowa closed-set sentence test (Level A), and a parent questionnaire. Results: The scores on the Telephone Profile and Iowa closed-set sentence test significantly increased between the pre-training assessment and the assessments at 3 and 6 months. The results on the Iowa closed-set sentence test significantly decreased between the 3- and the 6-month-post training assessments. The majority of parents reported 'slight improvement' in telephone skills after telephone training. No improvement was reported by the majority of parents in the use of repair strategies during telephone conversations. Discussion: Telephone training provided by a special education professional appears effective in prelingually deafened children with a CI. Home training provided by parents is less effective, but helps maintain the skills acquired in the professional telephone training. Conclusion: Structured telephone training provided by a professional improves telephone skills in children with a CI. Repair strategies for telephone use should be incorporated into rehabilitation programmes for CI users.